2022
DOI: 10.1089/jmf.2021.k.0138
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid-Enriched Extract of RipePrunus mume(Siebold) Siebold & Zucc. Induces Laxative Effects by Regulating the Expression of Aquaporin 3 and Prostaglandin E2in Rats with Loperamide-Induced Constipation

Abstract: Previously, we demonstrated that extracts of the ripe fruit (rPM) and unripe fruit (uPM) of Prunus mume (Siebold) Siebold & Zucc. and citric acid have a laxative effect, which is at least partially mediated by the increase in fecal parameters as seen in the low-fiber diet-induced constipation model rats. This study aims at investigating the laxative effects of citric acid-enriched aqueous extracts of rPM, uPM, and its active compounds, such as citric acid and malic acid, on loperamide-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Choi et al reported that vanillic acid could significantly enhance the amplitude and frequency of contractile responses of the isolated rat colon in vitro . 45 In Na et al 's study, 46 malic acid significantly increased the relief of Lop-induced constipation in rats and the secretion of mucin in the colon. Therefore, the effect of increasing goblet cells to secrete mucin of L. acidipiscis YJ5 in our study may be mainly related to its organic acid metabolites.…”
Section: Discussionmentioning
confidence: 92%
“…Choi et al reported that vanillic acid could significantly enhance the amplitude and frequency of contractile responses of the isolated rat colon in vitro . 45 In Na et al 's study, 46 malic acid significantly increased the relief of Lop-induced constipation in rats and the secretion of mucin in the colon. Therefore, the effect of increasing goblet cells to secrete mucin of L. acidipiscis YJ5 in our study may be mainly related to its organic acid metabolites.…”
Section: Discussionmentioning
confidence: 92%
“…Although the kombucha drink used in our study underwent pasteurization during the production process [ 19 ], rendering it unable to function as a probiotic, we cannot rule out the potential additive positive effects of organic acids and other bioactive components present in the kombucha drink itself. Several experimental studies have demonstrated that acetic, lactic, malic or citric acids can regulate bowel movements through different mechanisms, including the increase of prostaglandin E 2 secretion and decreased expression of aquaporin 3 [ 31 , 32 ]. The kombucha drink we utilized in our study contains several organic acids (for example, acetic, malic, citric, lactic, and tartaric) in substantial amounts, which explains the relatively low pH value (3.57) of the drink [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the laxative effects of Maren pills ( Zhan et al, 2020 ) or Pekinenin C ( Yu et al, 2018 ) in alleviating constipation may be associated with the increased expression of AQP3 via nuclear factor κB (NF-κB) signal pathway. Moreover, a recent study reported that the citric acid-enriched extract of ripe Prunus mume (Siebold) effectively improved the symptoms of constipation without causing diarrhea and tolerance by regulating the expression of AQP3 and prostaglandin E2 in the rat colons ( Na et al, 2022 ).…”
Section: Role Of Aqp3 In Constipation and Regulation Of Laxatives On ...mentioning
confidence: 99%